1990
DOI: 10.1159/000226796
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Pirarubicin (THP-Adriamycin) in Metastatic Breast Cancer Patients

Abstract: Fourteen patients with metastatic breast cancer previously treated with one chemotherapy regimen received Pirarubicin at a dose of 70 mg/m2 at 3-week intervals. In 7 patients the dose had to be reduced, in 1 patient to 40 mg/m2 and in 6 patients to 50–60 mg/m2. There were 1 complete and 2 partial remissions. These objective responses were observed in soft tissue, lung and pleural areas and lasted 1+; 4+ and 5+ months. Grade 3 and 4 leukopenia was found in 42%, grade 3 thrombocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…In our study, which combined cytarabine with ATRA and anthracyclines both in induction and consolidation, the long‐term outcome was improved and showed a low CIR level. Moreover, by adopting prarubicin (Lenk et al , 1990) and aclarubicin (Warrell, 1986), two agents of anthracyclines with relatively low acute cardiotocicity, the cumulative doses of anthracycllines were lowered to levels that did not exceed moderate dosages (approximately 300–550 mg/m 2 ). Late abnormalities of left ventricular performance were uncommon with cumulative anthracycline doses <300 mg/m 2 , but late cardiotoxicity might be an important concern in patients with moderate or higher dosages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, which combined cytarabine with ATRA and anthracyclines both in induction and consolidation, the long‐term outcome was improved and showed a low CIR level. Moreover, by adopting prarubicin (Lenk et al , 1990) and aclarubicin (Warrell, 1986), two agents of anthracyclines with relatively low acute cardiotocicity, the cumulative doses of anthracycllines were lowered to levels that did not exceed moderate dosages (approximately 300–550 mg/m 2 ). Late abnormalities of left ventricular performance were uncommon with cumulative anthracycline doses <300 mg/m 2 , but late cardiotoxicity might be an important concern in patients with moderate or higher dosages.…”
Section: Discussionmentioning
confidence: 99%
“…Long‐term adverse effects, including cardiotoxicity and secondary malignancy, were surveyed through followe‐up analysis. For evaluation of the potential risk of cardiotoxicity, cumulative doses of anthracyclines were converted to equivalent doses of daunorubicin using ratios in 1:3–1:5 for idarubicin/mitoxantrone, 1:1·6 for pirarubicin, and 1:0·2 for aclarubicin (Warrell, 1986; Lenk et al , 1990; Sakata‐Yanagimoto et al , 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Lenk et al [32] reported a trial in 14 patients with metastatic breast cancer, 5 of them pretreated with one chemotherapy regimen, who were treated with 70 mg/m2 of pirarubicin every 3 weeks. The dose needed to be reduced to 50-60 mg/m2 in 6 patients and to 40 mg/m2 in I patient.…”
Section: Breast Cancermentioning
confidence: 99%
“…Pirarubicin differs distinctly from other anthracyclines in pharmacodynamic properties, and has a far greater distribution volume (3) and therefore it produces less cardiac toxicity than DXR, epirubicin or mitoxantrone (4). Several Phase II trials have confirmed its anti‐tumor activity in breast cancer (5–7), hematological malignancies (8), and other solid tumors (9–11).…”
mentioning
confidence: 99%